The comparison of common cancer types and the coincidence of concomitant chronic diseases between palliative home care patients in Lodz Voivodeship and the general Polish population - Ciałkowska-Rysz, Aleksandra (Termedia Publishing House, 2012)
INTRODUCTION: The continued growth in the number of elderly with cancer and age-related chronic diseases will cause in Poland an increase in demand for palliative care. The aim of the study was to identify chronic comorbidities and cancer types in palliative home care patients and to compare their incidence with the general Polish population. MATERIAL AND METHODS: The data was obtained from 543 patients who received palliative home care between 2005-2009. The occurrence of the most common chronic conditions such as arterial hypertension, ischemic heart disease, diabetes, chronic pulmonary diseases and central nervous system diseases were analysed together with the cancer types. RESULTS: The study group included 259 women (47.7%) and 284 men (52.3%) aged 25-91 years old. The most common primary neoplasm locations for men were lung (28.2% vs. 21.4% in general population) and colorectal cancer (18.7% vs. 11.4% in general population), and in women breast (19.7% vs. 22.8% in general population) and colorectal cancer (17.4% vs. 9.2% in general population). The incidence of ischemic heart disease, diabetes, and chronic pulmonary diseases was significantly different in comparison to the general populations (47.0% vs. 11.3%; 20.3% vs. 6.8%; 16.6% vs. 27.5%, respectively). The mean number of concomitant diseases was 1.6 for women and 1.8 for men vs. 1.7 and 1.2 in the general Polish population respectively. CONCLUSIONS: The majority of the patients had concomitant disease, with cardiovascular diseases being most common. The most common primary neoplasm diagnoses in palliative home care patients were lung and colorectal cancer, which corresponds to the cancer prevalence in the general population.